The Influence of Product Quality on Woman Fashion Caluellathelabel of Purchase Decision Through Shopee E-commerce - Larasati, Irene Putri; Budiman, Arief; Fauziyah, Azizah (A Social Science and Entrepreneurship Journal, 2023)
The purpose of this research is to determine the influence of product quality on Caluellathelabel consumer purchasing decisions. This study uses quantitative data analysis involving 72 samples, namely consumer of Caluellathelabel. The result of this research is that there is a positive and significant influence between product quality (X) on purchasing decision (Y). This is known by conducting a t-test which states there is positive correlation or significant influence between product quality on purchasing decision at Caluellathelabel through shopee e-commerce.